Low Densities of the Ghost Crab Ocypode quadrata Related to Large Scale Human Modification of Sandy Shores - Barboza, Carlos A. M.; Mattos, Gustavo; Soares-Gomes, Abílio; Zalmon, Ilana Rosental; Costa, Leonardo Lopes (Frontiers in Marine Science, 2021)
Sandy beaches are the most common ecosystems of coastal regions and provide direct and indirect essential services for millions of people, such as coastal protection, fishing, tourism and recreational activities. However, the natural habitats of sandy shores are being modified at rates never experienced before, making beaches key monitoring sites of marine ecosystems worldwide. The unique ghost crab species Ocypode quadrata is the most conspicuous crustacean of sandy beaches along the Western Atlantic coast and has been successfully used as an indicator of anthropogenic and environmental variability. Using the existing literature and unpublished data, we compiled a dataset including burrows density from 164 beach sectors covering the entire range of the species distribution. Our aim was to investigate the response of densities to key drivers of the species’ distribution, including levels of natural habitat modification of sandy beaches, human population size, nightlight intensity, primary productivity, wave energy, sediment grain size, seasons, sea surface and air temperatures. Our results showed that most studies are concentrated at sub-tropical and temperate regions. The use of burrows counts is the principal proxy used to estimate density. At a continental scale, we found negative effects of natural habitat modification in the density of crab populations. For the first time, widely used indicators of land urbanization, such as human population size and nightlight intensity, were related to lower values of ghost crabs densities. Sea surface temperature and primary productivity were positively and negatively related to the number of burrows, respectively. A weak effect was attributed to grain size. Finally, there is clear evidence in the scientific literature indicating that ghost crabs are valuable targets for protection actions on sandy beaches that can benefit coexisting species and provide natural habitat conservation.